A Critical Overview of the Use of Platelet-Rich Plasma in Equine Medicine Over the Last Decade - Camargo Garbin, Livia; Lopez, Catalina; Carmona, Jorge U. (Frontiers in Veterinary Science, 2021)
In the 1990s, the role of platelets in inflammation and tissue healing was finally recognized. Since then, the clinical use of platelet-derived products (hemocomponents), such as, platelet-rich plasma (PRP), markedly increased. The promise of a more economical option of a disease-modifying treatment led to the intensive and continuous research of PRP products and to its widespread clinical use. A number of protocols and commercial kits have been developed with the intention of creating a more practical and reliable option for clinical use in equine patients. Still, the direct comparison between studies is particularly challenging due to the lack of standardization on the preparation methods and product composition. The incomplete reports on PRP cellular concentration and the poorly designed in vivo studies are additional matters that contest the clinical efficiency of this biomaterial. To overcome such challenges, several in vitro and in vivo studies have been proposed. Specifically, experiments have greatly focused in protocol optimization and its effect in different tissues. Additionally, in vivo studies have proposed different biological products envisioning the upgrade of the anti-inflammatory cytokines trusting to increase its anti-inflammatory effect. The individual variability and health status of the animal, type of tissue and condition treated, and protocol implemented are known to influence on the product's cell and cytokine composition. Such variability is a main clinical concern once it can potentially influence on PRP's therapeutic effects. Thus, lack of qualitative and quantitative evidence-based data supporting PRP's clinical use persists, despite of the numerous studies intended to accomplish this purpose. This narrative review aims to critically evaluate the main research published in the past decade and how it can potentially impact the clinical use of PRP.